Orientation system for people with cognitive disabilities - Ramos, João Ricardo Martins (2012)
In health care there has been a growing interest and investment in various forms of constant individuals monitoring. The increasing of average life expectation and, consequently, the costs in health care due to elderly population are the motivation for this investment. However, health monitoring is not only important to elderly people, it can be also applied to people with cognitive disabilities. Health monitoring can be developed based on Ambient Intelligence applications which are physically versatile and user friendly, i.e., the system can perform their tasks without causing panic to the user, providing comfort and pleasure to use.